Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.3201/eid1504.080664
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Chikungunya and Dengue Virus Infections during Simultaneous Outbreaks, Gabon, 2007

Abstract: An outbreak of febrile illness occurred in Gabon in 2007, with 20,000 suspected cases. Chikungunya or dengue-2 virus infections were identified in 321 patients; 8 patients had documented co-infections. Aedes albopictus was identified as the principal vector for the transmission of both viruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
184
0
16

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(211 citation statements)
references
References 14 publications
3
184
0
16
Order By: Relevance
“…21 We documented the simultaneous presence of CHIKV, dengue virus, and leptospirosis infection in the community as well as the concurrent presence of CHIKV and dengue antibodies in same subjects. 22,23 However, the contribution of leptospiral and dengue viral infection in the present outbreak is low, which is evidenced by low seropositivity to these infections among the patients affected during the outbreak.…”
mentioning
confidence: 90%
“…21 We documented the simultaneous presence of CHIKV, dengue virus, and leptospirosis infection in the community as well as the concurrent presence of CHIKV and dengue antibodies in same subjects. 22,23 However, the contribution of leptospiral and dengue viral infection in the present outbreak is low, which is evidenced by low seropositivity to these infections among the patients affected during the outbreak.…”
mentioning
confidence: 90%
“…[9][10][11] In India, concurrent isolation of CHIKV and DENV had been reported since 1964 from different States. 2,9 In 2010, a hospital-based study revealed co-circulation of CHIKV and DENV in some areas of West Bengal, India with high morbidity.…”
mentioning
confidence: 99%
“…Though previous records of concurrent infections of dengue and chikungunya (Myers and Carey, 1967;Leroy et al, 2009;Chang et al, 2010;Harendra et al, 2009) and concurrent infections of dengue and malaria (Charrel, 2005;Hati et al, 2012) exist, this is the first ever report of concurrent infections of dengue, chikungunya and malaria (P. falciparum).…”
Section: Introductionmentioning
confidence: 99%
“…In serial blood specimens collected from this patient the authors demonstrated an increase in antibody against both the viruses mentioned. Concurrent dengue virus and chikungunya virus infections during simultaneous outbreaks in Gabon in Africa in 2007 were documented, where either dengue-2 virus or chikungunya infections were identified in 321 patients at molecular level applying PCR technique, of which 8 had co-infections (Leroy et al, 2009). Concurrent isolation of dengue virus and chikungunya virus from a confirmed case imported from Singapore was described in Taiwan; the virus was detected through antibody neutralization and plaque purification techniques (Chang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%